Scots law tales - Grant, John P.; Sutherland, Elaine (Dundee : Dundee University Press, 2010)
This volume reveals the stories behind some of the most important and memorable cases in Scottish legal history. It brings these leading cases from the Scottish courts to life by capturing the personalities involved, describing the events leading up to each case, detailing what the courts decided and why, and explaining the role that each case played in the development of Scottish law.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Law -- Scotland -- Cases; Justice, Administration of -- Scotland -- Cases; Courts -- Scotland -- Cases; Law; Laws of specific jurisdictions & specific areas of law